THE IMPACT OF ACCREDITATION ON PERCEIVED SERVICE QUALITY IN EDUCATIONAL INSTITUTIONS: A STRATEGIC PERSPECTIVE - Husna, Fatimatul; Holifah (International Journal of Multidisciplinary Reseach, 2025)
This study examines how accreditation affects perceived service quality in schools, specifically looking at the strategy at SMP Nurul Jadid. In today's era, accreditation is essential to build public trust in educational institutions. We used a qualitative case study method, collecting data from observations, in-depth interviews with principals, teachers, students, and parents, and reviewing official documents. The main results of this study indicate that "A" accreditation acts as a major driver that changes many things. First, accreditation increases school trust and reputation, serves as tangible evidence of quality, influences parents' decisions, and generates pride within the school. Second, accreditation becomes a strategic key to obtain more resources and establish new partnerships, which ultimately improve school facilities and programs. Third, accreditation encourages the development of a curriculum that is more appropriate and focused on student needs, triggering innovation in teaching. However, we also found that there were various opinions from teachers, protests from some members of the community, and varied student academic results. This means that for accreditation to be truly successful, schools need good change management strategies, effective communication, and special attention to the needs of all parties. Academically, this study provides new insights by linking accreditation with Signaling Theory, Legitimacy Theory, and Social Capital Theory to explain how accreditation works at the junior high school level, filling a gap in research that often focuses on higher education. The limitations of this study are that it only takes one school sample and does not delve too deeply into the differences between groups of people. Therefore, further studies that are broader and use a variety of methods would be very helpful in making more targeted education policies.